A participação da infância na política local: limitações e reflexões - Mollet, Juliana Montenegro Brasileiro [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
This doctoral thesis analyses, from a critical psychosocial perspective, the limits and possibilities of institutional political participation by children and adolescents in the contemporary context, marked by the crisis of representative democracy and the expansion of democratic innovations aimed at broadening citizen participation. Despite regulatory advances that recognise children and adolescents as subjects of rights, current discourses and practices have not yet translated into substantive transformations in terms of their integration as citizens. This thesis proposes an analysis that focuses on the psychosocial dimensions of the participation of children and adolescents in contemporary society. The research is based on a theoretical framework that articulates Critical Theory of Democracy, Marxist Theory of the State and Citizenship, Critical Social Psychology, and Participatory and Deliberative Theory of Democracy. From these approaches, participation is conceived as a space of conflict and dispute in which possibilities open up. To answer the research questions, the thesis is structured in three complementary studies. Study 1: a scoping review that examines the contributions of social psychology to the study of democratic innovations. The results show that, although there are relevant contributions, scientific production is scattered and mainly concentrated on adult populations. Gaps in the analysis of child participation are thus identified, as well as a lack of articulation between deliberation, emotions, social identity and power relations. Study 2: discursively analyses normative documents on social assistance policy in Brazil. The results highlight transformations in institutional language, which increasingly incorporates references to rights, citizenship and participation. However, these changes coexist with formulations that maintain paternalistic conceptions of childhood, but with a discourse that integrates neoliberal vocabulary. It is concluded that this limits the political influence of children and adolescents. Study 3: empirically examines a deliberative process in schools in Spain, focusing on the relationship between prior emotional dispositions, positions on climate change and polarisation. The results show that polarisation, both in its thematic and affective dimensions, is strongly conditioned by the participants' prior emotional dispositions, and that deliberation can modify thematic polarisation, but not affective polarisation. Likewise, group composition (homogeneous or enclave groups versus heterogeneous or mixed groups) does not generate the expected effects: homogeneous groups do not become radicalised and heterogeneous groups do not show reductions in affective polarisation. Overall, the thesis shows that the institutional political participation of children and adolescents cannot be understood in isolation from the emotions, social identities and structural power inequalities that permeate it. Far from constituting automatic solutions to polarisation or political exclusion, democratic innovations require designs that are sensitive to these dimensions and a reconceptualisation of children and adolescents as full-fledged political subjects.

Esta tese de doutorado analisa, a partir de uma perspectiva psicossocial crítica, os limites e possibilidades da participação política institucional de crianças e adolescentes no contexto contemporâneo, marcado pela crise da democracia representativa e pela expansão de inovações democráticas voltadas para ampliar a participação cidadã. Apesar dos avanços regulatórios que reconhecem crianças e adolescentes como sujeitos de direitos, os discursos e práticas atuais ainda não se traduziram em transformações substantivas em termos de sua integração como cidadãos. Esta tese propõe uma análise que se concentra nas dimensões psicossociais da participação de crianças e adolescentes na sociedade contemporânea. A pesquisa baseia-se em um marco teórico que articula a Teoria Crítica da Democracia, a Teoria Marxista do Estado e da Cidadania, a Psicologia Social Crítica e a Teoria Participativa e Deliberativa da Democracia. A partir dessas abordagens, a participação é concebida como um espaço de conflito e disputa no qual se abrem possibilidades. Para responder às questões de pesquisa, a tese está estruturada em três estudos complementares. Estudo 1: uma revisão exploratória que examina as contribuições da psicologia social para o estudo das inovações democráticas. Os resultados mostram que, embora existam contribuições relevantes, a produção científica é dispersa e concentra-se principalmente em populações adultas. Assim, são identificadas lacunas na análise da participação infantil, bem como uma falta de articulação entre deliberação, emoções, identidade social e relações de poder. Estudo 2: analisa discursivamente documentos normativos sobre a política de assistência social no Brasil. Os resultados destacam transformações na linguagem institucional, que incorpora cada vez mais referências a direitos, cidadania e participação. No entanto, essas mudanças coexistem com formulações que mantêm concepções paternalistas da infância, mas com um discurso que integra vocabulário neoliberal. Conclui-se que isso limita a influência política de crianças e adolescentes. Estudo 3: examina empiricamente um processo deliberativo em escolas na Espanha, com foco na relação entre disposições emocionais prévias, posições sobre mudanças climáticas e polarização. Os resultados mostram que a polarização, tanto em sua dimensão temática quanto afetiva, é fortemente condicionada pelas disposições emocionais prévias dos participantes, e que a deliberação pode modificar a polarização temática, mas não a polarização afetiva. Da mesma forma, a composição do grupo (grupos homogêneos ou enclaves versus grupos heterogêneos ou mistos) não gera os efeitos esperados: os grupos homogêneos não se radicalizam e os grupos heterogêneos não apresentam reduções na polarização afetiva. No geral, a tese mostra que a participação política institucional de crianças e adolescentes não pode ser entendida isoladamente das emoções, identidades sociais e desigualdades estruturais de poder que a permeiam. Longe de constituir soluções automáticas para a polarização ou exclusão política, as inovações democráticas exigem projetos sensíveis a essas dimensões e uma reconceitualização das crianças e adolescentes como sujeitos políticos plenos.

Esta tesis doctoral analiza, desde una perspectiva psicosocial crítica, los límites y las posibilidades de la participación política institucional de niños, niñas y adolescentes en el contexto contemporáneo, marcado por la crisis de la democracia representativa y la expansión de innovaciones democráticas orientadas a ampliar la participación ciudadana. A pesar de los avances normativos que reconocen a la infancia y la adolescencia como sujetos de derechos, los discursos y las prácticas actuales aún no se traducen en transformaciones sustantivas cuanto a su integración como ciudadano. Esta tesis propone un análisis que sitúa en el centro las dimensiones psicosociales de la participación de NNA en la contemporaneidad. La investigación se apoya en un marco teórico que articula la Teoría Crítica de la Democracia, la Teoría Marxista del Estado y la Ciudadanía y la Psicología Social Crítica y la Teoría Participativa y Deliberativa de la Democracia. Desde estos enfoques, la participación se concibe como un espacio de conflicto y disputa en el que se abren posibilidades. Para responder a las preguntas de investigación, la tesis se estructura en tres estudios complementarios. Estudio 1: scoping review que examina las contribuciones de la Psicología Social al estudio de las innovaciones democráticas. Los resultados muestran que, aunque existen aportes relevantes, la producción científica es dispersa y se concentra mayoritariamente en poblaciones adultas. Se identifican así vacíos en el análisis de la participación infantil, así como una escasa articulación entre deliberación, emociones, identidad social y relaciones de poder. Estudio 2: analiza discursivamente documentos normativos de la política de Asistencia Social en Brasil. Los resultados destacan las transformaciones en el lenguaje institucional, que incorpora de forma creciente referencias a derechos, ciudadanía y participación. No obstante, estos cambios conviven con formulaciones que mantienen concepciones tutelares de la infancia, pero con un discurso que integra el vocabulario neoliberal. Se concluye que eso limita la capacidad de incidencia política de niños, niñas y adolescentes. Estudio 3: examina empíricamente un proceso deliberativo en centros escolares en España, centrándose en la relación entre disposiciones emocionales, posicionamientos sobre el cambio climático y polarización. Los resultados muestran que la polarización, tanto en su dimensión temática como afectiva, está fuertemente condicionada por las emocionales previas de los participantes, y que la deliberación puede modificar la polarización temática, pero no la afectiva. Asimismo, la composición grupal (grupos homogéneos o enclave frente a grupos heterogéneos o mixtos) no genera los efectos esperados: los grupos homogéneos no se radicalizan y los heterogéneos no evidencian reducciones en la polarización afectiva. En conjunto, la tesis muestra que la participación política institucional de la infancia y la adolescencia no puede comprenderse al margen de las emociones, las identidades sociales y las desigualdades estructurales de poder que la atraviesan. Lejos de constituir soluciones automáticas frente a la polarización o la exclusión política, las innovaciones democráticas requieren diseños sensibles a estas dimensiones y una reconceptualización de niños y adolescentes como sujetos políticos de pleno derecho.
La participación de la infancia en la política local: limitaciones y reflexiones
Keywords: Psicologia social; Participação política; Infância e juventude; Democracia; Assistência Social; Psicología social; Participación política; Asistencia Social; Infancia y juventud